Process for recycling a platinum, palladium and rhodium-containing spent catalyst
Patent Information
- Application Number
- CN202611164155.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-08-03
AI Technical Summary
[0006]针对现有技术的不足,本发明提供了一种含铂钯铑废催化剂的回收再利用工艺,解决了现有干法气化回收工艺中因废催化剂积碳导致的传质受阻,以及后续固相捕集阶段吸收剂表面易形成钝化层进而影响贵金属提取率和试剂利用率的问题
1.本发明通过在反应体系中加入含氟混卤改性扩孔助剂,并结合变温变压脉冲循环处理,改善了废催化剂因积碳造成的孔隙堵塞问题。含氟助剂受热释放的氟组分对催化剂载体产生局部蚀刻形成次生微孔隙,配合变温变压脉冲处理时的压力变化,利用压力梯度将孔隙内部蓄积的贵金属气态络合物向外排送,降低了传质阻力,提高了贵金属的气化提取率;
Smart Images

Figure CN122669217B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of waste catalyst recycling and treatment technology, specifically a recycling and reuse process for platinum, palladium, and rhodium-containing waste catalysts. Background Technology
[0002] Platinum, palladium, rhodium, and other precious metals are widely used in chemical catalysis, and spent catalysts at the end of their service life are important secondary resources of these precious metals. Currently, the dry gas-phase extraction process is commonly used for the recycling and treatment of such spent catalysts. This process mainly utilizes solid halogenating reagents to convert the precious metals in the catalyst into gaseous components under heating conditions, causing them to volatilize and separate from the support. These gaseous components are then captured by a solid absorbent, thereby obtaining a solid double salt precursor powder enriched with precious metals. The entire process is primarily a gas-solid reaction, mainly producing solid powder materials.
[0003] During long-term service, spent catalysts are prone to carbon buildup on their surface and within the pores of the support, and the supported precious metal components often undergo high-temperature sintering and agglomeration. In existing dry gas-phase extraction processes, carbon buildup in the support pores can cause pore blockage, leading to increased mass transfer resistance to the escape of gaseous complexes generated internally. The difficulty in venting gaseous products from the pores can cause localized increases in gas phase saturation, limiting further gasification reactions and affecting the extraction and volatilization of precious metals.
[0004] In the subsequent gas-phase capture stage of dry processes, solid absorbents such as potassium chloride are often used to react with gaseous volatiles for capture. The noble metal double salt precipitate generated by the reaction usually adheres to the outer surface of the solid absorbent particles. As the capture process proceeds, the surface precipitate gradually increases and forms a crystalline shell, which easily encapsulates the unreacted solid absorbent inside. This product encapsulation phenomenon hinders the contact between the gaseous components and the fresh interface inside the absorbent, causing the reaction to stagnate, reducing the conversion rate of the solid absorbent, and affecting the overall capture efficiency of the process.
[0005] Therefore, the present invention provides a process for recycling and reusing platinum, palladium and rhodium-containing waste catalysts to overcome the shortcomings of the prior art. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a process for recycling and reusing platinum, palladium, and rhodium-containing waste catalysts. This process solves the problems in existing dry gasification recovery processes, such as mass transfer obstruction caused by carbon buildup in waste catalysts, and the formation of a passivation layer on the surface of the absorbent during the subsequent solid-phase trapping stage, which affects the extraction rate of precious metals and the utilization rate of reagents.
[0007] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a process for recycling and reusing platinum-palladium-rhodium spent catalysts. In this invention, the spent catalyst powder is platinum-palladium-rhodium spent catalyst powder, and the following technical solution is adopted: A process for recycling and reusing platinum-palladium-rhodium spent catalysts includes the following steps: S1. After drying the waste catalyst powder, it is mixed with anhydrous aluminum trichloride, anhydrous ferric trichloride, ammonium chloride and fluorine-containing mixed halogen modified pore-expanding aid in a closed equipment to obtain a solid mixed reaction material. The fluorine-containing mixed halogen modified pore-expanding aid is a fluorine-containing polymer micro powder. S2. Potassium chloride and natural flake graphite are physically blended and pre-placed in the second collection temperature zone of the rotary reactor as a solid collection bed. S3. The solid mixed reaction material described in step S1 is continuously and sealed into the first reaction temperature zone of the rotary reactor. Dry carrier gas is introduced into the rotary reactor to allow the fluorine-containing mixed halogen modified pore-expanding agent to release fluorine-containing components when heated in the first reaction temperature zone. 3 to 5 cycles of variable temperature and pressure pulse cyclic treatment are continuously performed in the first reaction temperature zone. S4. The reaction carrier gas carrying the gaseous noble metal halide complex enters the second collection temperature zone of the rotary reactor. Under mechanical stirring, the gaseous material passes through the solid collection bed and undergoes a metathesis precipitation reaction with potassium chloride in the solid collection bed at the gas-solid interface. S5. The carrier gas then enters the third condensation and recovery temperature zone of the rotary reactor, where the sublimable gaseous material sublimates on the wall to form a reusable solid powder, and the reusable solid powder is returned to step S1 for recycling. The unsublimated gas is recycled after being cleaned and dehumidified. S6. After the reaction cycle is completed, the solid residue in the first reaction temperature zone is discharged, and the solid collection bed material in the second collection temperature zone is unloaded to obtain the noble metal complex salt precursor powder loaded on the graphite skeleton material. The noble metal complex salt is formed by the metathesis precipitation reaction of gaseous noble metal halide complex and potassium chloride.
[0008] Anhydrous ferric chloride and anhydrous aluminum chloride are used for gas-phase complexation extraction, combined with a fluorine-containing mixed halide modified pore-expanding agent and natural flake graphite, and subjected to variable temperature and pressure pulse treatment. This can improve mass transfer conditions and alleviate interface passivation to a certain extent, thereby enhancing the recovery effect of precious metals. It should be noted that in the process system of this invention, the closed equipment can be a mixing device capable of closed mixing, such as a closed ball mill mixing device, a closed mixing tank, or other closed containers that can reduce the entry of moisture. The drying carrier gas is preferably an inert gas such as dry nitrogen or dry argon to prevent hydrolysis of gaseous chlorination reagents and precious metal complexes during high temperature and transport. The precious metal complex salt precursor powder refers to a solid powder containing precious metal complex salts, formed by the metathesis precipitation reaction of gaseous precious metal halide complexes and potassium chloride, and loaded on a graphite framework material. In this process, it can specifically include potassium hexachloroplatinate, potassium tetrachloropalladate, and rhodium-containing complex salt precipitates. The specific reaction process and mechanism are mainly reflected as follows: The addition of anhydrous ferric chloride to the system provides a localized oxidation environment, which helps to oxidize and chlorinate platinum, palladium, and rhodium, which are mainly in zero-valent metal states in the spent catalyst. Anhydrous aluminum trichloride acts as a complexing agent, combining with noble metal chlorides to form gaseous noble metal halide complexes with a certain vapor pressure, promoting the desorption and volatilization of noble metals from the catalyst support surface. The reaction process generally conforms to the following general chemical formula (where M represents platinum, palladium, or rhodium): Oxidative chlorination reaction: M + xFeCl3 → MCl x +xFeCl2; Complexation vaporization reaction: MCl x +yAlCl3→MAl y Cl (x+3y) (Gaseous state); In the aforementioned gasification extraction process, the fluorine-containing mixed-halogen modified pore-expanding aid undergoes thermal decomposition under heating conditions in the first reaction temperature zone, releasing fluorine components. These fluorine components react with the carbon deposits on the surface of the spent catalyst and the silicon-aluminum support framework, causing localized micro-etching and forming secondary micropores. These secondary micropores help to open up channels affected by carbon deposits, allowing gaseous complexes to escape outwards along the micropores. Based on this, combined with variable-temperature and variable-pressure pulsed cycling treatment, the contact between the reactant gas and the solid catalyst can often be increased during the pressurization phase, while during the depressurization phase, the pressure gradient difference drives the gaseous complexes accumulated inside the micropores to escape, thereby reducing local saturation and promoting the forward gasification reaction.
[0009] As the gas stream carrying gaseous noble metal halide complexes enters the second collection temperature zone, the gaseous material undergoes a metathesis precipitation reaction with potassium chloride, as shown in the following general formula: MAl y Cl (x+3y) (Gaseous) + nKCl (Solid) → KnMCl (x+n)(Solid precipitate) + yAlCl3 (gaseous); In the gas-solid reaction process, natural flake graphite consists of sheet-like particles with interlayer cleavage. Utilizing its interlayer cleavage structure and self-lubricating properties, natural flake graphite undergoes interlayer shear slip under mechanical stirring. This shear stress acts on the complex salt precipitate layer attached to the surface of the potassium chloride particles, causing mechanical exfoliation of the product's crystalline shell, thereby continuously exposing the unreacted interfaces of potassium chloride. This interface renewal mechanism helps alleviate reaction stagnation caused by product encapsulation, further improving the conversion efficiency of the absorbent.
[0010] Specifically, limiting the variable temperature and pressure pulsed cyclic treatment to 3 to 5 cycles can better balance gasification extraction efficiency and process energy consumption. If the number of cycles is less than 3, it is difficult to form a sufficient alternating extraction effect on the gaseous complexes accumulated deep in the pores, which can easily lead to some precious metals remaining inside the carrier. If the number of cycles exceeds 5, it will not only increase the system's heat consumption and operating time, but also result in diminishing marginal returns to the improvement of precious metal extraction rate. Furthermore, excessive pulsed gas flow can easily lead to excessive pulverization of the spent catalyst skeleton, increasing the load on downstream gas-solid separation.
[0011] Preferably, in step S1, for every 100 parts by weight of waste catalyst powder, 15-25 parts by weight of anhydrous aluminum trichloride, 2-4 parts by weight of anhydrous ferric trichloride, 5-10 parts by weight of ammonium chloride, and 1-5 parts by weight of fluorine-containing mixed halogen modified pore-expanding agent are added; in step S2, for every 100 parts by weight of waste catalyst powder, the corresponding pre-set amount of potassium chloride is 10-20 parts by weight, and the amount of natural flake graphite is 30-60 parts by weight.
[0012] Controlling the range of formulation components is generally beneficial for maintaining the oxidation potential and complexing agent concentration in the reaction system at an appropriate level. Excessive chlorination reagent will increase the load on the downstream condensation and recovery temperature zone and easily lead to material agglomeration, while insufficient chlorination may affect the extraction degree of zero-valent precious metals. Limiting the ratio of potassium chloride to natural flake graphite can enable the dispersion medium in the solid bed to have corresponding mechanical grinding and interlayer exfoliation efficiency, maintaining the renewal of the reaction interface. Ammonium chloride can be used as an auxiliary chlorine source and chlorination atmosphere conditioning component in this system. During the heating process, it helps to maintain the chlorination environment of the reaction system and, together with anhydrous aluminum trichloride and anhydrous ferric trichloride, promotes the oxidative chlorination and gas-phase complexation migration of precious metal components.
[0013] Preferably, in step S1, the platinum-palladium-rhodium spent catalyst powder is pretreated as follows: the platinum-palladium-rhodium spent catalyst powder is placed in an environment of 120-150℃ and dried at a constant temperature for 2-4 hours to control its free water content to be reduced to less than 0.5wt% based on the total mass of the platinum-palladium-rhodium spent catalyst powder.
[0014] Because the removal of a large amount of free water adsorbed in the pores of the spent catalyst powder can, to some extent, prevent the anhydrous aluminum trichloride and anhydrous ferric trichloride from hydrolyzing during the heating stage to generate oxides and hydrogen chloride gas, thus helping to maintain the chemical activity of the gaseous complex extraction reagent.
[0015] Preferably, in step S1, the preparation method of the fluorinated mixed halogen modified pore-expanding agent includes: vacuum drying industrial waste fluoropolymer scraps after surface cleaning to constant weight at 80-100℃; then performing deep cryogenic mechanical pulverization using liquid nitrogen at -196℃ as the cooling medium; finally, classifying the fluoropolymer micro powder with a median particle size D50 of 50-100μm using an air classifier; wherein the fluoropolymer is selected from polytetrafluoroethylene or perfluoroethylene propylene.
[0016] Cryogenic mechanical pulverization of fluoropolymer waste using liquid nitrogen improves the problems of polymer amorphization and decreased crystallinity caused by frictional heat during room temperature pulverization. The micropowder prepared under cryogenic conditions maintains a high degree of crystallinity, causing it to typically undergo thermal decomposition and release fluorine active components only after entering the high-temperature zone of the first reaction temperature. This ensures that the micro-etching and pore-expanding effect occurs within the temperature zone where precious metal complexes volatilize, which to some extent improves the utilization of the additive. The fluorinated mixed-halogen modified pore-expanding additive refers to fluoropolymer micropowder that releases fluorine components upon heating in the first reaction temperature zone, is used to locally micro-etch and expand the pores of waste catalysts, and participates in the gas-phase mixed-halogen coordination regulation. Preferred micropowders are polytetrafluoroethylene (PTFE) micropowder or perfluoroethylene propylene (PFEP) micropowder.
[0017] Preferably, in step S3, the specific operation of a single cycle of the variable temperature and pressure pulse cycle treatment is as follows: control the material temperature in the first reaction zone at 350-370℃, adjust the exhaust volume at the tail end to maintain an absolute pressure of 0.10-0.11MPa inside the first reaction zone, and maintain constant temperature and pressure for 15-20 minutes; then raise the temperature to 440-460℃ at a heating rate of 15-25℃ / min, and simultaneously reduce the exhaust volume to raise the gas pressure inside the first reaction zone to an absolute pressure of 0.14-0.16MPa within 3.6-6 minutes, and maintain this temperature and pressure for 5-10 minutes; then cut off the heating source, increase the flow of drying carrier gas and simultaneously increase the exhaust volume, start the external cooling unit, and within 5-10 minutes, pump the pressure inside the first reaction zone back down to an absolute pressure of 0.10-0.11MPa, and lower the temperature back to 350-370℃.
[0018] The initial isothermal operation is mainly used for material mixing and primary chlorination of the surface in the chemical reaction within the system; the subsequent heating and pressurization cause the system to transition to a supersaturated vapor pressure state; the subsequent cooling and extraction form a negative pressure gradient, which uses pressure changes to extract gaseous noble metal halide complexes deep in the pores into the main gas flow, helping to reduce secondary deposition.
[0019] Preferably, in step S4, the temperature of the second collection zone is maintained constant at 150-200℃, and the mechanical stirring is controlled to be a low-speed stirring at 5-15 rpm; in step S5, the temperature of the condensation wall in the third condensation recovery zone is controlled at 10-50℃.
[0020] Maintaining a collection temperature of 150-200℃ ensures that the byproduct aluminum trichloride and free fluorine-containing sublimable gaseous substances are transported downstream in a gaseous state, reducing the impact of their condensation on the solid bed. The low-speed stirring of 5-15 rpm is adapted to the physical properties of natural flake graphite, providing surface shearing and stripping force while reducing powder dust and carrier gas entrainment losses caused by high speed. The third condensation recovery temperature zone is set at 10-50℃, which is conducive to the sublimation and reuse of unreacted chlorinating agent powder.
[0021] Preferably, in step S6, the obtained precious metal complex salt precursor powder is a solid mixture, which contains unreacted natural flake graphite framework and potassium chloride, as well as potassium hexachloroplatinate, potassium tetrachloropalladate and rhodium-containing enriched precipitates attached to the interface between potassium chloride and graphite.
[0022] By utilizing the gas-solid metathesis mechanism, the noble metal components in the original waste catalyst system are enriched and transferred to the solid mixed matrix, realizing the phase transformation of the noble metals and providing a high-quality solid precursor for the subsequent preparation of high-temperature alloying materials. Since the content of the rhodium component is relatively low and the dispersion is high, a clear rhodium-containing crystalline phase main peak may not appear in the X-ray diffraction pattern. Its presence in the solid trapping powder can be confirmed by detecting the enrichment of rhodium elements by ICP-MS. Therefore, this invention describes it as a rhodium-enriched precipitate or a rhodium-enriched component.
[0023] Preferably, in step S6, the performance parameters of the obtained noble metal complex salt precursor powder are controlled to meet the following: in the thermogravimetric analysis (TGA) test conducted under dry air atmosphere, with the noble metal complex salt precursor powder linearly heated from 25°C to 1000°C at a rate of 10°C / min, the main aerobic oxidation weight loss range is between 500°C and 750°C; and the mass percentage content of carbon in the noble metal complex salt precursor powder is greater than or equal to 40.0% based on the total mass of the noble metal complex salt precursor powder, and the mass percentage content of silicon in the noble metal complex salt precursor powder is less than or equal to 0.1% based on the total mass of the noble metal complex salt precursor powder.
[0024] The obtained powder exhibits the oxidative weight loss characteristics of the graphite phase in a specific temperature range. A carbon content of ≥40.0% allows the accompanying natural flake graphite components to participate in the reaction as carbon-based additives during the subsequent high-temperature alloying process. Simultaneously, a silicon content of ≤0.1% indicates that the process effectively separates the precious metal from the spent catalyst silicon-aluminum support framework, significantly reducing interference from silicon-based inorganic impurities in subsequent material processing and improving the purity of the final product.
[0025] In the aforementioned general reaction formula, x, y, and n are all positive integers that satisfy chemical balancing and the coordination number of the complex. Their specific values depend on the type of noble metal M and its stable coordination state in gas-phase complexing and solid-phase precipitation environments.
[0026] For the uncondensed gas in step S5, the impurity removal and dehumidification operation specifically refers to passing the tail gas into an alkaline absorption tower for washing to remove residual gaseous aluminum chloride and hydrogen fluoride and other acidic halide gases, and then removing moisture through a molecular sieve or anhydrous calcium chloride and other desiccants, thereby ensuring the purity of the carrier gas returned to the front end for recycling and avoiding water vapor interference with the gaseous extraction process.
[0027] Furthermore, the carbon content by mass percentage in this invention can be determined by combustion infrared carbon-sulfur analysis, and the silicon content by mass percentage can be determined by X-ray fluorescence spectroscopy; the thermogravimetric analysis and oxidation weight loss range can be determined by thermogravimetric-differential scanning calorimetry under dry air atmosphere; the presence of potassium hexachloroplatinate and potassium tetrachloropalladate in the obtained mixture can be identified by X-ray diffraction, and the enrichment of rhodium by ICP-MS can be used to confirm the presence of rhodium complex salt precipitates or rhodium-containing components.
[0028] This invention provides a process for recycling and reusing platinum-palladium-rhodium spent catalysts. It has the following beneficial effects: 1. This invention improves the pore blockage problem caused by carbon buildup in spent catalysts by adding a fluorinated mixed halogen modified pore-expanding agent to the reaction system and combining it with variable temperature and pressure pulsed cycling treatment. The fluorine component released by the fluorinated agent upon heating causes local etching of the catalyst support, forming secondary micropores. Combined with the pressure changes during variable temperature and pressure pulsed treatment, the pressure gradient is used to expel the gaseous complexes of precious metals accumulated inside the pores, reducing mass transfer resistance and improving the gasification and extraction rate of precious metals. 2. This invention reduces the formation of a dense passivation layer on the absorbent surface during the gas-solid reaction stage by using a mixture of potassium chloride and natural flake graphite as the solid bed in the trapping temperature zone. Under mechanical stirring, the natural flake graphite utilizes its interlayer cleavage structure to generate shear slip, physically peeling away the double salt precipitate layer attached to the surface of the potassium chloride particles, exposing the unreacted potassium chloride to the reaction interface, thereby improving the conversion and utilization rate of the absorbent. 3. This invention employs anhydrous ferric chloride and anhydrous aluminum trichloride synergistically for dry gas-phase complexation extraction, avoiding the drawbacks of high oxidant consumption and long process time in wet leaching. Anhydrous ferric chloride oxidizes and chlorinates zero-valent precious metals, while anhydrous aluminum trichloride combines with them to form gaseous precious metal halide complexes, which are then transferred outwards. Finally, a complex salt precursor powder is obtained in the collection zone. The carbon component remaining in this powder can be directly used as a reducing agent in subsequent pyrometallurgical processes, achieving comprehensive utilization of the materials. Attached Figure Description
[0029] Figure 1 High-resolution spectra of Pt 4f samples at different reaction stages of this invention; Figure 2 This is a characteristic signal diagram of the carrier gas in the later stage of the reaction according to the present invention; Figure 3 This is a graph showing the changes in system pressure and characteristic ion response intensity during the variable temperature and pressure pulse processing of this invention. Figure 4 The XRD pattern of the noble metal complex salt-graphite composite precursor powder of the present invention; Figure 5 This is a comparison chart of the gas phase extraction rates of platinum, palladium, and rhodium in this invention; Figure 6 This is a graph showing the change in the concentration of gaseous precious metals escaping from the outlet of the solid trapping bed according to the present invention. Figure 7 This is a thermogravimetric oxidation weight loss curve of the solid trapping powder product of the present invention. Detailed Implementation
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0032] The spent catalyst powder is taken from depleted motor vehicle exhaust purification catalysts or chemical synthesis catalysts. Its matrix support is cordierite or alumina, and the active component loaded on the surface includes at least one of platinum, palladium or rhodium. In the following examples, the spent catalyst powder contains three precious metal components: platinum, palladium and rhodium. Its phase state may include oxidized state, elemental zero-valent state or a mixture of the two.
[0033] Anhydrous aluminum trichloride has the CAS number 7446-70-0, and its purity is greater than or equal to 98 wt% and its moisture content is less than or equal to 0.5 wt%.
[0034] Anhydrous ferric chloride has the CAS number 7705-08-0, and its purity is greater than or equal to 98 wt% and its moisture content is less than or equal to 0.5 wt%.
[0035] The ammonium chloride has the CAS number 12125-02-9 and a purity of ≥99wt%.
[0036] Polytetrafluoroethylene (PTFE) scrap, CAS number 9002-84-0, is a polymer compound formed by the polymerization of tetrafluoroethylene, with the structural formula —[CF2—CF2]. n — It is a homopolymer with a linear structure, a crystallinity of 90% to 95%, and a density of 2.1 g / cm³. 3 Up to 2.3 g / cm 3 , refers to waste generated from industrial extrusion or machining.
[0037] The CAS number for perfluoroethylene propylene scrap is 25067-11-2. It is a polymer compound copolymerized from tetrafluoroethylene and hexafluoropropylene, belonging to the random copolymer category, with a density of 2.12 g / cm³. 3 Up to 2.17 g / cm 3 , refers to waste generated during industrial processing.
[0038] The potassium chloride has the CAS number 7447-40-7 and a purity of ≥99wt%. In this invention, coarse particles with a particle size distribution in the range of 1mm to 3mm after sieving are specifically selected.
[0039] The natural flake graphite, CAS number 7782-42-5, is a hexagonal layered crystalline carbon with a fixed carbon content of ≥95wt%. In this invention, coarse particles with a particle size distribution in the range of 2mm to 5mm after sieving are specifically selected.
[0040] The high-purity quartz sand has CAS number 14808-60-7 and a silica content of ≥99wt%. In this invention, coarse particles with a particle size distribution in the range of 2mm to 5mm after sieving are specifically selected.
[0041] In this specific embodiment, the internal pressure of the reactor is measured in absolute pressure. The operating pressure range is close to atmospheric pressure, from 0.10 MPa to 0.11 MPa, and from 0.105 MPa to 0.11 MPa corresponds to a slightly positive pressure condition.
[0042] Preparation Example 1: This preparation example provides a method for preparing a fluorine-containing mixed halogen modified pore-expanding agent, comprising the following steps: (1) Take industrial waste polytetrafluoroethylene scraps, clean them with deionized water by ultrasonic cleaning to remove surface mechanical oil stains, and dry them in a vacuum drying oven at 90°C until constant weight; (2) The dried material is fed into a cryogenic pulverizer and cryogenically pulverized under the condition of -196℃ liquid nitrogen as the cooling medium; (3) After pulverization, the polytetrafluoroethylene micro powder with a median particle size D50 of 75 μm is collected by air classifier to obtain the fluorine-containing mixed halogen modified pore-expanding agent.
[0043] Preparation Example 2: This preparation example provides a method for preparing a fluorine-containing mixed halogen modified pore-expanding agent, comprising the following steps: (1) Take industrial waste polytetrafluoroethylene scraps, ultrasonically clean them with deionized water to remove surface mechanical oil stains, and dry them in a vacuum drying oven at 80°C until constant weight; (2) The dried material is fed into a cryogenic pulverizer and cryogenically pulverized under the condition of -196℃ liquid nitrogen as the cooling medium; (3) After pulverization, the polytetrafluoroethylene micro powder with a median particle size D50 of 50 μm is collected by air classifier to obtain the fluorine-containing mixed halogen modified pore-expanding agent.
[0044] Preparation Example 3: This preparation example provides a method for preparing a fluorine-containing mixed halogen modified pore-expanding agent, comprising the following steps: (1) Take industrial waste polytetrafluoroethylene propylene scraps, ultrasonically clean them with deionized water to remove surface mechanical oil stains, and dry them in a vacuum drying oven at 100°C until constant weight; (2) The dried material is fed into a cryogenic pulverizer and cryogenically pulverized under the condition of -196℃ liquid nitrogen as the cooling medium; (3) After pulverization, the polytetrafluoroethylene propylene micro powder with a median particle size D50 of 100 μm is collected to obtain the fluorinated mixed halogen modified pore-expanding agent.
[0045] Example 1: This example provides a process for recycling and reusing platinum-palladium-rhodium spent catalysts, including the following steps: (1) Weigh 100 parts by weight of waste catalyst powder and place it in a drying oven at 135°C for 3 hours to dry it at a constant temperature until the free water content is reduced to below 0.5 wt%. In a drying room with a relative humidity of less than or equal to 5%, place the dried waste catalyst powder, 20 parts by weight of anhydrous aluminum trichloride, 3 parts by weight of anhydrous ferric trichloride, 8 parts by weight of ammonium chloride, and 3 parts by weight of the fluorine-containing mixed halogen modified pore-expanding agent obtained in Preparation Example 1 into a closed ball mill mixing device and mix them in a closed ball mill for 45 minutes to obtain a uniform solid mixed reaction material; (2) 15 parts by weight of potassium chloride and 45 parts by weight of natural flake graphite are physically blended and pre-placed in the second collection temperature zone of the rotary reactor as a solid collection bed. (3) The solid mixed reactant is continuously and sealed and fed into the first reaction temperature zone of the rotary reactor, and dry nitrogen gas with a flow rate of 10 L / min is introduced into the system. Four cycles of variable temperature and pressure pulsed cyclic treatment were continuously performed in the first reaction zone. The specific operation of a single cycle was as follows: the material temperature in the first reaction zone was controlled at 360℃, and the exhaust frequency of the exhaust fan at the tail of the reactor was adjusted to maintain a slight positive pressure of 0.105MPa inside the first reaction zone for 18 minutes. Then, the temperature of the first reaction zone was increased to 450℃ at a heating rate of 20℃ / min, while the exhaust volume of the exhaust fan at the tail was reduced, so that the internal pressure increased to 0.15MPa in about 4.5 minutes. After the material temperature in the first reaction zone reached 450℃, it was maintained at this temperature and pressure for 8 minutes. Then, the heating source was cut off, the amount of room temperature dry nitrogen introduced was increased, and the exhaust volume of the exhaust fan was increased simultaneously. At the same time, the external cooling unit of the first reaction zone was started, and the internal pressure was pumped back to 0.105MPa and the temperature dropped back to 360℃ within 8 minutes. (4) The reaction carrier gas carrying the gaseous precious metal halide complex enters the second collection temperature zone of the rotary reactor. The second collection temperature zone is kept at a low speed of 10 rpm with mechanical stirring to keep the temperature of the second collection temperature zone constant at 175°C. When the gaseous material passes through the solid collection bed, a metathesis precipitation reaction occurs at the gas-solid interface to generate precious metal halide complex potassium salt precipitate. The by-product gaseous components continue to be discharged downstream. (5) The carrier gas enters the third condensation recovery temperature zone of the rotary reactor. The condensation wall temperature of the third condensation recovery temperature zone is controlled at 30°C. The sublimable gaseous substances are sublimated on the wall of the third condensation recovery temperature zone to form solid mixed powder. The mechanical scraper is started to collect the solid powder and return it to the batching process of step (1) for recycling. The unsublimated gas is purified and dehumidified in sequence by the alkaline absorption unit, the fluorine-containing component absorption unit and the silica gel drying tower, and then transported by the compressor to the system inlet for recycling. (6) After the reaction cycle is completed, the solid residue of the first reaction temperature zone is discharged through the slag discharge valve, and the solid collection bed material of the second collection temperature zone is unloaded. The resulting dry mixed powder is the noble metal complex salt precursor powder loaded on the graphite skeleton material.
[0046] Example 2: This example provides a process for recycling and reusing platinum-palladium-rhodium spent catalysts, including the following steps: (1) Weigh 100 parts by weight of waste catalyst powder and place it in a drying oven at 120°C for 4 hours to dry it at a constant temperature until the free water content is reduced to below 0.5 wt%. In a drying room with a relative humidity of less than or equal to 5%, place the dried waste catalyst powder, 15 parts by weight of anhydrous aluminum trichloride, 2 parts by weight of anhydrous ferric trichloride, 5 parts by weight of ammonium chloride, and 1 part by weight of the fluorine-containing mixed halogen modified pore-expanding agent obtained in Preparation Example 2 into a closed ball milling mixing device and mix them in a closed ball milling for 60 minutes to obtain a uniform solid mixed reaction material; (2) 10 parts by weight of potassium chloride and 30 parts by weight of natural flake graphite are physically blended and pre-placed in the second collection temperature zone of the rotary reactor as a solid collection bed. (3) The solid mixed reactant is continuously and sealed and fed into the first reaction temperature zone of the rotary reactor, and dry nitrogen gas with a flow rate of 5 L / min is introduced into the system. Three cycles of variable temperature and pressure pulse cyclic treatment were continuously performed in the first reaction temperature zone. The specific operation of a single cycle was as follows: the material temperature in the first reaction temperature zone was controlled at 350℃, and the exhaust frequency of the exhaust fan at the tail of the reactor was adjusted to maintain a near-normal pressure of 0.10MPa inside the first reaction temperature zone for 20 minutes. Then, the temperature of the first reaction temperature zone was increased to 440℃ at a heating rate of 15℃ / min, while the exhaust volume of the exhaust fan at the tail was reduced, so that the internal pressure increased to 0.14MPa in about 6 minutes. After the material temperature in the first reaction temperature zone reached 440℃, it was maintained at this temperature and pressure for 10 minutes. Then, the heating source was cut off, the amount of room temperature dry nitrogen introduced was increased, and the exhaust volume of the exhaust fan was increased simultaneously. At the same time, the external cooling unit of the first reaction temperature zone was started, and the internal pressure was pumped back to 0.10MPa and the temperature dropped back to 350℃ within 10 minutes. (4) The reaction carrier gas carrying the gaseous precious metal halide complex enters the second collection temperature zone of the rotary reactor. The second collection temperature zone is kept at a low speed of 5 rpm by mechanical stirring. The temperature of the second collection temperature zone is kept constant at 150℃. When the gaseous material passes through the solid collection bed, a metathesis precipitation reaction occurs at the gas-solid interface to generate potassium salt of precious metal halide complex. The by-product gaseous components continue to be discharged downstream. (5) The carrier gas enters the third condensation recovery temperature zone of the rotary reactor. The condensation wall temperature of the third condensation recovery temperature zone is controlled at 10°C. The sublimable gaseous substances are sublimated on the wall of the third condensation recovery temperature zone to form solid mixed powder. The mechanical scraper is started to collect the solid powder and return it to the batching process of step (1) for recycling. The unsublimated gas is purified and dehumidified in sequence by the alkaline absorption unit, the fluorine-containing component absorption unit and the silica gel drying tower, and then transported by the compressor to the system inlet for recycling. (6) After the reaction cycle is completed, the solid residue of the first reaction temperature zone is discharged through the slag discharge valve, and the solid collection bed material of the second collection temperature zone is unloaded. The resulting dry mixed powder is the noble metal complex salt precursor powder loaded on the graphite skeleton material.
[0047] Example 3: This example provides a process for recycling and reusing platinum-palladium-rhodium spent catalysts, including the following steps: (1) Weigh 100 parts by weight of waste catalyst powder and place it in a drying oven at 150°C for 2 hours to dry it at a constant temperature until the free water content is reduced to below 0.5 wt%. In a drying room with a relative humidity of less than or equal to 5%, place the dried waste catalyst powder, 25 parts by weight of anhydrous aluminum trichloride, 4 parts by weight of anhydrous ferric trichloride, 10 parts by weight of ammonium chloride, and 5 parts by weight of the fluorine-containing mixed halogen modified pore-expanding agent obtained in Preparation Example 3 into a closed ball milling mixing device and mix them in a closed ball milling for 30 minutes to obtain a uniform solid mixed reaction material; (2) 20 parts by weight of potassium chloride and 60 parts by weight of natural flake graphite are physically blended and pre-placed in the second collection temperature zone of the rotary reactor as a solid collection bed. (3) The solid mixed reactant is continuously and sealed and fed into the first reaction temperature zone of the rotary reactor, and dry nitrogen gas with a flow rate of 15 L / min is introduced into the system. Five cycles of variable temperature and pressure pulsed cyclic treatment were continuously performed in the first reaction zone. The specific operation of a single cycle was as follows: the material temperature in the first reaction zone was controlled at 370℃, and the exhaust frequency of the exhaust fan at the tail of the reactor was adjusted to maintain a slight positive pressure of 0.11MPa inside the first reaction zone, and the constant temperature and pressure were maintained for 15 minutes; then the temperature of the first reaction zone was increased to 460℃ at a heating rate of 25℃ / min, and the exhaust volume of the exhaust fan at the tail was reduced simultaneously, so that the internal pressure increased to 0.16MPa within about 3.6 minutes. After the material temperature in the first reaction zone reached 460℃, it was maintained at this temperature and pressure for 5 minutes; then the heating source was cut off, the amount of room temperature dry nitrogen introduced was increased and the exhaust volume of the exhaust fan was increased simultaneously, and the external cooling unit of the first reaction zone was started, so that the internal pressure was pumped back to 0.11MPa and the temperature dropped back to 370℃ within 5 minutes; (4) The reaction carrier gas carrying the gaseous precious metal halide complex enters the second collection temperature zone of the rotary reactor. The second collection temperature zone is kept at a low speed of 15 rpm with mechanical stirring to keep the temperature of the second collection temperature zone constant at 200℃. When the gaseous material passes through the solid collection bed, a metathesis precipitation reaction occurs at the gas-solid interface to generate precious metal halide complex potassium salt precipitate. The by-product gaseous components continue to be discharged downstream. (5) The carrier gas enters the third condensation recovery temperature zone of the rotary reactor. The condensation wall temperature of the third condensation recovery temperature zone is controlled at 50°C. The sublimable gaseous substances are sublimated on the wall of the third condensation recovery temperature zone to form a solid mixed powder. The mechanical scraper is started to collect the solid powder and return it to the batching process of step (1) for recycling. The unsublimated gas is purified and dehumidified in sequence by the alkaline absorption unit, the fluorine-containing component absorption unit and the silica gel drying tower, and then transported by the compressor to the system inlet for recycling. (6) After the reaction cycle is completed, the solid residue of the first reaction temperature zone is discharged through the slag discharge valve, and the solid collection bed material of the second collection temperature zone is unloaded. The resulting dry mixed powder is the noble metal complex salt precursor powder loaded on the graphite skeleton material.
[0048] Example 4: This example provides a process for recycling and reusing platinum-palladium-rhodium spent catalysts, including the following steps: (1) Weigh 100 parts by weight of heavily aged waste petrochemical catalyst powder. The catalyst surface of this batch is covered with a dense carbon deposit layer, and the platinum, palladium and rhodium noble metal components loaded are mainly in the state of zero-valent metals that are difficult to extract due to high temperature sintering. Place it in a drying oven at 135°C and dry it at a constant temperature for 3 hours to reduce its free water content to below 0.5 wt%. In a drying room with a relative humidity of less than or equal to 5%, place the dried waste petrochemical catalyst powder, 20 parts by weight of anhydrous aluminum trichloride, 3 parts by weight of anhydrous ferric chloride, 8 parts by weight of ammonium chloride and 3 parts by weight of the fluorine mixed halogen modified pore-expanding agent obtained in Preparation Example 1 into a closed ball mill mixing device and mix them in a closed ball mill for 45 minutes to obtain a uniform solid mixed reaction material. (2) 15 parts by weight of potassium chloride and 45 parts by weight of natural flake graphite are physically blended and pre-placed in the second collection temperature zone of the rotary reactor as a solid collection bed. (3) The solid mixed reactant is continuously and sealed and fed into the first reaction temperature zone of the rotary reactor, and dry nitrogen gas with a flow rate of 10 L / min is introduced into the system. Four cycles of variable temperature and pressure pulsed cyclic treatment were continuously performed in the first reaction zone. The specific operation of a single cycle was as follows: the material temperature in the first reaction zone was controlled at 360℃, and the exhaust frequency of the exhaust fan at the tail of the reactor was adjusted to maintain a slight positive pressure of 0.105MPa inside the first reaction zone for 18 minutes. Then, the temperature of the first reaction zone was increased to 450℃ at a heating rate of 20℃ / min, while the exhaust volume of the exhaust fan at the tail was reduced, so that the internal pressure increased to 0.15MPa in about 4.5 minutes. After the material temperature in the first reaction zone reached 450℃, it was maintained at this temperature and pressure for 8 minutes. Then, the heating source was cut off, the amount of room temperature dry nitrogen introduced was increased, and the exhaust volume of the exhaust fan was increased simultaneously. At the same time, the external cooling unit of the first reaction zone was started, and the internal pressure was pumped back to 0.105MPa and the temperature dropped back to 360℃ within 8 minutes. (4) The reaction carrier gas carrying the gaseous precious metal halide complex enters the second collection temperature zone of the rotary reactor. The second collection temperature zone is kept at a low speed of 10 rpm with mechanical stirring to keep the temperature of the second collection temperature zone constant at 175°C. When the gaseous material passes through the solid collection bed, a metathesis precipitation reaction occurs at the gas-solid interface to generate precious metal halide complex potassium salt precipitate. The by-product gaseous components continue to be discharged downstream. (5) The carrier gas enters the third condensation recovery temperature zone of the rotary reactor. The condensation wall temperature of the third condensation recovery temperature zone is controlled at 30°C. The sublimable gaseous substances are sublimated on the wall of the third condensation recovery temperature zone to form solid mixed powder. The mechanical scraper is started to collect the solid powder and return it to the batching process of step (1) for recycling. The unsublimated gas is purified and dehumidified in sequence by the alkaline absorption unit, the fluorine-containing component absorption unit and the silica gel drying tower, and then transported by the compressor to the system inlet for recycling. (6) After the reaction cycle is completed, the solid residue of the first reaction temperature zone is discharged through the slag discharge valve, and the solid collection bed material of the second collection temperature zone is unloaded. The resulting dry mixed powder is the noble metal complex salt precursor powder loaded on the graphite skeleton material.
[0049] Comparative Example 1: This comparative example provides a recycling process for platinum, palladium, and rhodium-containing waste catalysts. The difference from Example 1 is that anhydrous ferric chloride is not added to the ingredients in step (1).
[0050] Apart from the differences mentioned above, the remaining steps and process conditions are the same as in Example 1.
[0051] Comparative Example 2: This comparative example provides a recycling process for platinum, palladium, and rhodium-containing waste catalysts. The difference from Example 1 is that the fluorine-containing mixed halogen modified pore-expanding agent obtained in Example 1 is not added to the ingredients in step (1).
[0052] Apart from the differences mentioned above, the remaining steps and process conditions are the same as in Example 1.
[0053] Comparative Example 3: This comparative example provides a recycling process for platinum, palladium, and rhodium-containing waste catalysts. The difference from Example 1 is that in step (3), variable temperature and pressure pulse cycle treatment is not performed. Instead, the material temperature in the first reaction zone is kept constant at 405°C, and the internal gas pressure is kept constant at 0.12 MPa. The process is continued for 154 minutes, so that the total processing time of the first reaction zone is consistent with that of Example 1.
[0054] Apart from the differences mentioned above, the remaining steps and process conditions are the same as in Example 1.
[0055] Comparative Example 4: This comparative example provides a recycling process for platinum, palladium, and rhodium-containing waste catalysts. The difference from Example 1 is that in step (2), high-purity quartz sand of equal weight is used to replace natural flake graphite in the solid trapping bed.
[0056] Apart from the differences mentioned above, the remaining steps and process conditions are the same as in Example 1.
[0057] Test Example 1: Experimental Description: This test utilizes a combination of staged sampling X-ray photoelectron spectroscopy analysis and online mass spectrometry detection to characterize the changes in the valence state of noble metals and the formation of gas-phase complex species within the first reaction temperature range. This is used to analyze the occurrence of gas-phase oxidation-chlorination and gas-phase mixed-halogen coordination reactions.
[0058] Experimental steps: (1) Solid materials from the first reaction temperature zone of Example 1, which were subjected to different temperature and pressure pulse cycle treatments, were extracted and labeled as initial stage samples, mid-reaction samples, and late-reaction samples, respectively. The solid samples were tested using an X-ray photoelectron spectrometer to obtain full-energy spectrum data with a scanning range of 0 eV to 1200 eV, and Pt 4f high-resolution spectral data were further acquired. Charge calibration was performed using the C 1s peak of surface contamination carbon as an internal standard, and peak fitting was performed on the Pt 4f7 / 2 and Pt 4f5 / 2 spectral peaks to obtain the relative surface distribution ratio of platinum valence states in samples at different stages. (2) When the system in Example 1 is running to the depressurization and extraction stage, the gas flow discharged from the outlet of the first reaction temperature zone is introduced into the detection chamber of the online quadrupole mass spectrometer through the halogen-resistant capillary tube. The scanning range is set to a mass-to-charge ratio of 1 to 800. The mass-to-charge ratio distribution signals of gaseous components corresponding to the solid sampling time nodes are continuously collected, and the normalized relative abundance of the corresponding characteristic mass-to-charge ratio is recorded. Combined with the isotopic distribution characteristics of platinum-containing, chlorine-containing, iron-containing and fluorine-containing ion peak clusters, the related characteristic signals of iron-aluminum-chlorine complex and the related characteristic signals of fluorine-chlorine mixed halide platinum-aluminum complex are assigned and analyzed.
[0059] The experimental data are shown in Table 1: .
[0060] According to Table 1 and Figure 1Test data shows that platinum in the catalyst material initially exists mainly in the zero-valent metallic state. The valence ratios in Table 1 represent the relative valence distribution of residual platinum on the surface and do not represent the absolute residual amount of platinum in the sample. As the temperature and pressure pulsed cycling treatment in the first reaction zone progresses, the proportion of zero-valent platinum on the surface of the solid sample decreases, while the proportion of high-valent platinum increases accordingly. This trend indicates that under the conditions of coexisting anhydrous aluminum trichloride, anhydrous ferric chloride, ammonium chloride, and fluorine-containing mixed halogen modified pore-expanding agent, and after being subjected to a temperature and pressure pulsed cycling condition of 360℃ micro-positive pressure in the first reaction zone, followed by heating to 450℃ and pressurizing to 0.15MPa, and then depressurizing and pumping back to 0.105MPa, there is a role in promoting the conversion of zero-valent platinum to high-valent platinum. Combining the sublimation characteristics of ferric chloride in the system and the subsequent changes in gas phase characteristic signals, it can be inferred that ferric chloride participates in the gas-phase oxidative chlorination process and contributes to the conversion of zero-valent precious metals to precious metal chloride precursors.
[0061] Simultaneous monitoring results from online mass spectrometry showed that the normalized relative abundance of the mass-to-charge ratio characteristic peaks belonging to iron-aluminum-chlorine complexes and fluorine-chlorine mixed-halogen platinum-aluminum complexes increased during the mid- and late-stage reactions in the exhaust stream. Combined with the mass-to-charge ratio distribution characteristics of the online mass spectrometry, it can be seen that gaseous complex characteristic signals related to iron, aluminum, chlorine, platinum, and fluorine appeared in the system. These results suggest that the fluorine-containing components released from polytetrafluoroethylene (PTFE) micropowder under heating conditions may participate in the gas-phase coordination process, causing some gaseous complexes to exhibit fluorine-chlorine mixed-halogen coordination characteristics.
[0062] The corresponding changes in the energy spectrum of the solid surface and the mass-to-charge ratio distribution of the gaseous components described above indicate a synergistic effect among the multi-component solid additives. Specifically, ferric chloride helps promote the oxidative chlorination conversion of zero-valent precious metals, and the fluorine-containing components released by the fluorine-containing additives can participate in the coordination structure regulation of the gas-phase complex, thereby reducing the apparent volatilization and migration resistance of the target precious metal complex. Therefore, this system is beneficial for deep pore encapsulation and the vaporization and migration of zero-valent metallic precious metals under relatively mild operating conditions.
[0063] Test Example 2: Experimental Description: This test aims to analyze the effect of variable temperature and pressure pulsed cyclic treatment on the gas phase mass transfer process and to characterize the transformation of solid components in the solid trapping bed.
[0064] Experimental steps: (1) An online mass spectrometry detection unit with a heat-insulated transmission pipeline is connected in series in the exhaust main line connecting the first reaction temperature zone and the second collection temperature zone of the system in Example 1. When the first cycle of variable temperature and pressure pulse cyclic processing is performed in Example 1, the online mass spectrometry detection unit is set to perform continuous time series sampling, and the pressure reading in the reactor at the current time node and the total response intensity of the characteristic ions of gaseous noble metal halide complexes in the corresponding outflow gas are recorded simultaneously; (2) The noble metal complex salt precursor powder collected in Example 1 was extracted as the solid sample to be tested. The sample was placed in an X-ray diffractometer for phase structure scanning. A copper Kα target was used as the X-ray source, and the diffraction angle scanning range was set to 10° to 80°, with a scanning rate of 5° / min. After obtaining the full spectrum data, the diffraction peak positions and relative intensities were compared and matched with the standard crystal diffraction database. Another portion of the sample was completely digested with a mixture of aqua regia and hydrofluoric acid and then brought to a final volume. The enrichment of rhodium in the solid trap powder was detected by ICP-MS.
[0065] The experimental data are shown in Table 2: ; ; .
[0066] According to Table 2 and Figure 2 Test data show that during the initial reaction temperature zone, in the isothermal and heating / pressurization stages under slight positive pressure, the total response intensity of characteristic ions of gaseous noble metal halide complexes in the exhaust gas stream remained at a low level. However, after the system entered the depressurization and extraction stage, the total response intensity of characteristic ions significantly increased, forming a response peak. This time-series change suggests that the pressure change generated during the depressurization and extraction stage helps enhance the outward migration of gaseous products within the pores, thereby reducing the resistance to mass transfer of products from the porous catalyst. These results support the conclusion that variable-temperature and variable-pressure pulsed cyclic treatment promotes the gas-phase migration of deep noble metal components within the pores.
[0067] Diffraction patterns of the product powder showed that, in addition to the pre-placed crystalline carbon and some unconsumed potassium chloride, potassium hexachloroplatinate and potassium tetrachloropalladate crystal diffraction signals were also detected in the solid material collected in the second trapping temperature zone. Due to the relatively low content and high dispersion of rhodium complex salts, no clear rhodium complex salt main peak appeared in the X-ray diffraction pattern; however, ICP-MS analysis showed that rhodium was enriched in the solid trapping powder. These results indicate that gaseous platinum and palladium halide complexes can undergo metathesis precipitation transformation with solid potassium chloride when passing through the solid trapping bed, forming relatively stable potassium noble metal chloride complex salts. Combined with the ICP-MS results, this supports the simultaneous trapping of the rhodium component by the solid trapping bed.
[0068] The combined results of the gas-phase response changes and solid-phase detection indicate a synergistic effect between the variable-temperature and variable-pressure pulsed cycling treatment and the metathesis-precipitation transformation in the solid trapping bed. The depressurization and extraction process helps remove the gaseous noble metal complexes generated in the reaction zone from the first reaction temperature zone, while the solid-phase transformation process in the solid trapping bed helps reduce the partial pressure of the noble metal complexes in the downstream gas phase. This synergistic effect promotes the volatilization and migration of noble metal components within the catalyst, enabling continuous extraction and trapping of noble metal components in an anhydrous dry process system.
[0069] Test Example 3: Experimental Description: This test aims to analyze the influence of process parameters on the gas-phase extraction rate of various precious metal elements by comparing the composition of reaction residues under different auxiliary agent components and operating pressure conditions.
[0070] Experimental steps: (1) Collect the initial untreated waste catalyst powder samples of the corresponding batches of Examples 1, 2, 3, 4, Comparative Examples 1, 2, and 3, as well as the solid residue samples discharged from the first reaction temperature zone after the reaction cycle of each group above, and pulverize them in a grinder to below 200 mesh to obtain homogeneous powder; (2) Accurately weigh each group of powder samples, place them in a microwave digestion vessel, add a mixture of aqua regia and hydrofluoric acid, and perform sample matrix digestion under the set temperature and pressure program. After digestion, remove the acid and make up the volume to prepare the aqueous phase solution to be tested; (3) The concentrations of platinum, palladium, and rhodium in the test solution were quantitatively determined using inductively coupled plasma mass spectrometry (ICP-MS). Based on the mass balance between the initial sample and the solid residue after the reaction, the gas-phase extraction rate of the target precious metal element in each group was calculated. The gas-phase extraction rate was calculated according to the following formula: Gas phase extraction rate / % = (Total amount of target precious metal element in the initial sample - Total amount of target precious metal element in the solid residue after reaction) / Total amount of target precious metal element in the initial sample × 100%.
[0071] The experimental data are shown in Table 3: .
[0072] According to Table 3 and Figure 3 The results show that in Examples 1 to 4, the gas-phase extraction rates of platinum, palladium, and rhodium were generally at a high level. In contrast, in Comparative Example 1 without the addition of anhydrous ferric chloride, the extraction rates of all three precious metals were significantly reduced. These results suggest that under the test conditions, the introduction of anhydrous ferric chloride may help improve the conversion process of zero-valent precious metals to migratory chloride forms, thereby enhancing the gas-phase extraction efficiency of the target metals.
[0073] The spent catalyst sample used in Example 4 had carbon deposits on its surface, and the precious metal components were mainly in the zero-valent metal state. However, under the condition of a complete auxiliary agent system, its extraction results were still quite similar to those in Example 1. This result indicates that the method of the present invention still has a certain degree of adaptability to spent catalyst samples with high aging levels and difficult-to-treat precious metal forms.
[0074] In Comparative Example 2, without the addition of the fluorinated mixed halogen modified pore-expanding agent, the rhodium extraction rate was significantly lower than that of the Example Group, especially compared to Example 1. This result indicates that the addition of the fluorinated mixed halogen modified pore-expanding agent may significantly promote the vaporization and migration of the rhodium component. This may be because: firstly, the fluorinated component partially participates in coordination during the reaction, forming a fluorinated chlorine mixed halogen gaseous complex, which helps improve the volatilization and migration characteristics of the rhodium-related complex components; secondly, the components generated after the pyrolysis of the fluoropolymer may have a certain effect on the catalyst support surface, forming secondary pores, thereby helping to reduce the mass transfer resistance inside the pores.
[0075] In Comparative Example 3, which employed isothermal and isobaric operation, the gas-phase extraction rates of the three noble metals were all lower than those in Example 1, which used variable-temperature and variable-pressure pulsed cycling treatment. This comparative result indicates that, under the test conditions, variable-temperature and variable-pressure pulsed cycling treatment is beneficial for promoting the outward migration and expulsion of gaseous complexes generated inside the porous catalyst. For high-molecular-weight gaseous complexes formed deep within the pores, natural diffusion relying solely on concentration gradients results in a relatively low migration rate and is prone to localized secondary deposition; however, the pressure difference generated during the depressurization and extraction stage promotes the migration of these gaseous components from the reaction interface, thereby improving the overall gas-phase extraction efficiency.
[0076] Test Example 4: Experimental Description: This test aims to analyze the influence of different solid capture bed framework materials on the sustainability of gaseous noble metal component capture effect, and to evaluate the adaptability of the final solid capture product to subsequent processes.
[0077] Experimental steps: (1) During the first 120 minutes of operation in Example 1 and Comparative Example 4, a gas sampling point was set in the exhaust pipeline between the second trapping temperature zone and the third condensation recovery temperature zone. A cold trap absorption bottle containing a mixed absorbent of nitric acid and hydrochloric acid was used to quantitatively absorb the gas flowing through the outlet of the solid trapping bed. The absorption bottle was replaced every 20 minutes. After the collected absorbents from each time period were brought to a fixed volume, the total concentration of platinum, palladium and rhodium in the liquid was determined by inductively coupled plasma mass spectrometry. The concentration of gaseous precious metals escaping from the outlet of the solid trapping bed in the corresponding time period was calculated based on the sampling volume. (2) After the reaction process is completed, the final solid trapping powder products generated in the second trapping temperature zone of Example 1 and Comparative Example 4 are collected respectively. A portion of the powder is placed in the sample cell of an X-ray fluorescence spectrometer, and semi-quantitative scanning of major elements is performed under vacuum. The mass percentage of silicon in the product is recorded. Another portion of the powder is used to determine the mass percentage of carbon using a combustion infrared carbon-sulfur analyzer. (3) Take 15 mg of each of the two solid trapping powders mentioned above and place them in the alumina crucibles of the thermogravimetric-differential scanning calorimetry (TGC-DCC) instrument. Set the test atmosphere to dry air with a gas flow rate of 50 mL / min and the temperature program to linearly increase from room temperature (25 °C) to 1000 °C at a rate of 10 °C / min. Continuously record the percentage change in sample mass with temperature to obtain the thermogravimetric oxidation weight loss curve.
[0078] The experimental data are shown in Table 4: .
[0079] According to Table 4 and Figure 4 Test data showed that in the initial stage of the reaction, both Example 1 and Comparative Example 4, which used quartz sand as the bed skeleton material, exhibited low gaseous noble metal escape concentrations at the solid trapping bed outlet. As the reaction time increased, the gaseous noble metal escape concentration at the solid trapping bed outlet of Comparative Example 4 showed an increasing trend, while the escape concentration of Example 1 remained at a low level within the first 120 minutes of sampling. This result reflects that, compared with flake graphite beds, silica-based support materials are more prone to reaction interface passivation during long-cycle gas-solid reactions. The generated noble metal potassium chloride crystals can form a product deposition layer at the reaction interface. As the deposition layer thickens, the contact efficiency between unreacted potassium chloride and gaseous noble metal halide complexes decreases, making it easier for some gaseous noble metal halide complexes to penetrate the solid trapping bed and enter the downstream gas phase channel.
[0080] Example 1 improved the interfacial contact state within the solid trapping bed by introducing natural flake graphite. Graphite materials possess low interlayer shear resistance and certain solid-phase lubrication properties. Under the mechanical tumbling state of the solid trapping bed, the dispersed graphite flakes come into contact with and rub against the particles coated with complex salt deposits, potentially resulting in mechanical exfoliation, which helps to weaken the complex salt deposit layer on the particle surface. This interfacial renewal effect facilitates the continuous exposure of new reaction interfaces to the gas flow, thereby reducing the gas-solid reaction interface resistance, maintaining a high effective reaction interface area, and helping to reduce the gas-phase escape of the target noble metal component.
[0081] The results of testing the silicon and carbon content and thermogravimetric oxidation characteristics of the solid trapping powder products can be used to evaluate the impact of the bed skeleton material on the adaptability to subsequent processes. The trapping product of Comparative Example 4 contained a high proportion of silicon-based inorganic impurities, and no significant thermal weight loss was observed under high-temperature air atmosphere. When such trapping products containing silica impurities are used in conjunction with pyrometallurgical enrichment or wet dissolution processes, they may increase slag volume or introduce silica-like impurities. The trapping product of Example 1 retained a high proportion of carbon, and the thermogravimetric oxidation weight loss curve shows that the main aerobic oxidation weight loss range of this material is between 500℃ and 750℃. This result indicates that the obtained precious metal complex salt precursor powder has good process integration potential in subsequent metal smelting processes, and the associated carbon element can, to some extent, also play an auxiliary reduction role.
[0082] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A process for recycling and reusing platinum-palladium-rhodium spent catalysts, characterized in that, Includes the following steps: S1. After drying the platinum-palladium-rhodium waste catalyst powder, it is mixed with anhydrous aluminum trichloride, anhydrous ferric trichloride, ammonium chloride and fluorine-containing mixed halogen modified pore-expanding aid in a closed device to obtain a solid mixed reaction material. The fluorine-containing mixed halogen modified pore-expanding aid is a fluorinated polymer micro powder. S2. Potassium chloride and natural flake graphite are physically blended and pre-placed in the second collection temperature zone of the rotary reactor as a solid collection bed. S3. The solid mixed reaction material described in step S1 is continuously and sealed into the first reaction temperature zone of the rotary reactor. Dry carrier gas is introduced into the rotary reactor to allow the fluorine-containing mixed halogen modified pore-expanding agent to release fluorine-containing components when heated in the first reaction temperature zone. 3 to 5 cycles of variable temperature and pressure pulse cyclic treatment are continuously performed in the first reaction temperature zone. S4. The reaction carrier gas carrying the gaseous noble metal halide complex enters the second collection temperature zone of the rotary reactor. Under mechanical stirring, the gaseous material passes through the solid collection bed and undergoes a metathesis precipitation reaction with potassium chloride in the solid collection bed at the gas-solid interface. S5. The carrier gas then enters the third condensation and recovery temperature zone of the rotary reactor, where the sublimable gaseous material sublimates on the wall to form a reusable solid powder, and the reusable solid powder is returned to step S1 for recycling. The unsublimated gas is recycled after being cleaned and dehumidified. S6. After the reaction cycle is completed, the solid residue in the first reaction temperature zone is discharged, and the solid collection bed material in the second collection temperature zone is unloaded to obtain the noble metal complex salt precursor powder loaded on the graphite skeleton material. The noble metal complex salt is formed by the metathesis precipitation reaction of gaseous noble metal halide complex and potassium chloride. In step S1, for every 100 parts by weight of platinum, palladium and rhodium waste catalyst powder, add 15-25 parts by weight of anhydrous aluminum trichloride, 2-4 parts by weight of anhydrous ferric trichloride, 5-10 parts by weight of ammonium chloride and 1-5 parts by weight of fluorine mixed halogen modified pore-expanding agent. In step S2, for every 100 parts by weight of platinum, palladium, and rhodium waste catalyst powder, the corresponding amount of pre-set potassium chloride is 10-20 parts by weight, and the amount of natural flake graphite is 30-60 parts by weight. In step S1, the preparation method of the fluorinated mixed halogen modified pore-expanding agent includes: Industrial waste fluoropolymer scraps after surface cleaning are vacuum dried to constant weight at 80-100℃; then they are cryogenically pulverized using liquid nitrogen at -196℃ as the cooling medium; finally, they are classified by an air classifier, and fluoropolymer micro powder with a median particle size D50 of 50-100μm is collected; the fluoropolymer is selected from polytetrafluoroethylene or perfluoroethylene propylene.
2. The recycling and reuse process for platinum-palladium-rhodium spent catalysts according to claim 1, characterized in that, In step S1, the platinum-palladium-rhodium spent catalyst powder is pretreated as follows: the platinum-palladium-rhodium spent catalyst powder is placed in an environment of 120-150℃ and dried at a constant temperature for 2-4 hours to control its free water content to be reduced to less than 0.5wt% based on the total mass of the platinum-palladium-rhodium spent catalyst powder.
3. The recycling and reuse process for platinum-palladium-rhodium spent catalysts according to claim 1, characterized in that, In step S3, the specific operation of a single cycle of the variable temperature and pressure pulse cyclic processing is as follows: Control the material temperature in the first reaction zone at 350-370℃, adjust the exhaust volume at the tail end to maintain an absolute pressure of 0.10-0.11MPa inside the first reaction zone, and maintain constant temperature and pressure for 15-20 minutes; then raise the temperature to 440-460℃ at a heating rate of 15-25℃ / min, while simultaneously reducing the exhaust volume to raise the internal pressure of the first reaction zone to an absolute pressure of 0.14-0.16MPa within 3.6-6 minutes, and maintain this temperature and pressure for 5-10 minutes; then cut off the heating source, increase the flow of drying carrier gas and simultaneously increase the exhaust volume, start the external cooling unit, and within 5-10 minutes, pump the pressure inside the first reaction zone back down to an absolute pressure of 0.10-0.11MPa, and lower the temperature back to 350-370℃.
4. The recycling and reuse process for platinum-palladium-rhodium spent catalysts according to claim 1, characterized in that, The surface of the platinum-palladium-rhodium spent catalyst powder in step S1 contains a carbon deposit layer, and the noble metal components loaded on the platinum-palladium-rhodium spent catalyst powder are mainly in a zero-valent metal state.
5. The recycling and reuse process for platinum-palladium-rhodium spent catalysts according to claim 1, characterized in that, In step S2, the natural flake graphite is a sheet-like particle with an interlayer cleavage structure.
6. The recycling and reuse process for platinum-palladium-rhodium spent catalysts according to claim 1, characterized in that, In step S4, the temperature of the second collection zone is kept constant at 150-200℃, and the mechanical stirring is controlled to be a low-speed stirring with a rotation speed of 5-15 rpm. In step S5, the temperature of the condenser wall in the third condensation recovery zone is controlled between 10-50℃.
7. The recycling and reuse process for platinum-palladium-rhodium spent catalysts according to claim 1, characterized in that, In step S6, the obtained precious metal complex salt precursor powder is a solid mixture containing an unreacted natural flake graphite framework and potassium chloride, as well as potassium hexachloroplatinate, potassium tetrachloropalladate, and rhodium-containing enriched precipitates attached to the interface between potassium chloride and graphite.
8. The recycling and reuse process for platinum-palladium-rhodium spent catalysts according to claim 1, characterized in that, In step S6, the performance parameters of the obtained noble metal complex salt precursor powder are controlled to meet the following requirements: In a thermogravimetric analysis (TGA) test conducted under dry air atmosphere, with the temperature linearly increased from 25°C to 1000°C at a rate of 10°C / min, the main aerobic oxidation weight loss range was between 500°C and 750°C. Furthermore, the carbon content in the noble metal complex salt precursor powder, calculated as a percentage of the total mass of the precursor powder, was greater than or equal to 40.0%, and the silicon content, calculated as a percentage of the total mass of the precursor powder, was less than or equal to 0.1%.
Citation Information
Patent Citations
Method for extracting noble metal from waste vehicle exhaust catalyst
CN105256145A
Method for platinum group metals recovery from spent catalysts
CN110036122A